ANALISIS SISTEM PROTEKSI FEEDER EXPRESS GARDU INDUK SEI RAYA-GARDU HUBUNG KUALA DUA DENGAN MENGGUNAKAN FUNGSI FITUR GOOSE MESSAGE - ., Norman Suseno (Jurnal Teknik Elektro Universitas Tanjungpura, 2018)
Feeder Raya 2 and Raya 4 Gardu Induk Sei Raya is feeder express for electrical power source to Gardu Hubung Kuala Dua, on June 26th, 2016 which happened disruption in one of the feeder express which caused total outages at Gardu Hubung Kuala Dua because both of feeder express were experience the trip simultaneously. In electric power distribution system needed protection. The protection that used was Over Current Relay and Ground Fault Relay (OCR/GFR). This research was aimed to avoid total outages on Gardu Hubung Kuala Dua by evaluating the value setting relay OCR/GFR with standard inverse, by knowing the working time of relay toward the certain point disruption and by configuring the function of features IEC 61850 Goose Messages (Generic Object Oriented Substation Events) which exist on that relay teleprotection pattern, it was Direct Transfer Trip (DTT). Based on the literature that have been gained and also observation of the situation system in activity by simulations on the function features goose message. The result of calculation on coordination protection by using standardÂ  inverse, it obtained the working time relay more selective in each point of certain disruption and for working time relay used the function of features goose message, it obtained <100 Millisecond.Keywords : OCR/GFR, Teleprotection, Direct Transfer Trip (DTT), Goose Message, Coordination Value Of Setting Protection.